Constitutional Law Reform to Realize Inclusive Higher Education for Persons with Disabilities - Sapsudin, Asep; Qohar, Hendri Abdul (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Inclusive and equitable higher education is an urgency that cannot be overlooked, especially in efforts to guarantee the human rights of persons with disabilities. Legal reform is essential to create an educational environment that supports equal access, as mandated by Law No. 8 of 2016 and Government Regulation No. 13 of 2020. The persistent barriers, such as physical, social, and non-adaptive curricula, lead to inequitable access for persons with disabilities in higher education institutions. This reform is not only crucial to protect their rights but also to encourage their participation in broader social and economic development. This study aims to analyze the implementation of legal reform policies in creating inclusive access to higher education for persons with disabilities, as well as to identify the challenges still faced. The research employs a normative juridical method. The study finds that constitutional legal reform in Indonesia aims to ensure equal access to higher education for persons with disabilities through inclusive and non-discriminatory policies. Through regulations such as Law No. 8 of 2016 and Government Regulation No. 13 of 2020, the state is committed to providing disability-friendly facilities and adaptive curricula. This approach ensures that the rights of persons with disabilities are protected, allowing them to fully participate in higher education.